2023
DOI: 10.3389/fimmu.2023.1184252
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based target therapy in primary biliary cholangitis: opportunities before liver cirrhosis?

Abstract: Primary biliary cholangitis (PBC) is an immune-mediated liver disease characterized by cholestasis, biliary injuries, liver fibrosis, and chronic non-suppurative cholangitis. The pathogenesis of PBC is multifactorial and involves immune dysregulation, abnormal bile metabolism, and progressive fibrosis, ultimately leading to cirrhosis and liver failure. Ursodeoxycholic acid (UDCA) and obeticholic acid (OCA) are currently used as first- and second-line treatments, respectively. However, many patients do not resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 228 publications
(250 reference statements)
0
8
0
Order By: Relevance
“…PBC is a primary autoimmune disease of the liver that is more common in women, characterized by cholestasis, bile duct injury, cholangitis, and liver fibrosis, which can also lead to liver dysfunction, cirrhosis, or liver cancer [ 3 ]. PBC is also accompanied by extrahepatic autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…PBC is a primary autoimmune disease of the liver that is more common in women, characterized by cholestasis, bile duct injury, cholangitis, and liver fibrosis, which can also lead to liver dysfunction, cirrhosis, or liver cancer [ 3 ]. PBC is also accompanied by extrahepatic autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…ORMDL3 and GSDMB in chromosome 17q21 are associated with TD1 and primary biliary cirrhosis (19). Polymorphisms in the cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) gene are associated with susceptibility to PBC and TD1 (20,21). CTLA-4 is a negative regulator of T cell activation.…”
Section: Pbc and Type 1 Diabetesmentioning
confidence: 99%
“…CTLA-4 is a negative regulator of T cell activation. It can compete with CD28 and interact with the ligands B7-1 and B7-2 on antigen-presenting cells, affecting the induction and maintenance of T cells, especially the termination of peripheral T cell responses, to in uence susceptibility to type 1 diabetes and PBC (20,21). In the pathophysiological process, interferon alpha (INF-α) jointly participates in the occurrence and development of PBC and TD1 (22).…”
Section: Pbc and Type 1 Diabetesmentioning
confidence: 99%
“…To investigate the potential sources of heterogeneity in our study, we conducted meta-regression analysis since the I 2 values of the pooled sensitivity and specificity exceeded 50%. Various subgroups were defined based on sample size (< or more than 200), ethnicity (African, Asian, Caucasian, or multicenter), study period (published before or after 2010), and the detection Assassi [1] 2009 62.7 ± 7.81 America Clinical features* AMA/M2 IIF/ELISA 6 Bandin [2] 1996 NR France NR AMA IIF 8 Bargou [3] 2008 58.9 ± 13.4 Tunisia NR AMA/M2 IIF/ELISA 7 Cavazzana [4] 2011 48 ± 11.7 Italy EASL AMA IIF 8 Chung [5] 2016 53 (32-72) UK NR AMA ELISA 6 Dighiero [6] 1987 NR France NR AMA/M2 IIF/ELISA 5 Gabeta [7] 2007 62 (19-87) Greece Clinical features* AMA/M2 IIF/ELISA 8 Guatibonza-García [8] 2021 56.9 ± 10.2 Colombia Biopsy AMA IIF 5 Han [9] 2017 56.9 (28-85) Korea AASLD 2009 AMA/M2 IIF/ELISA 8 Hu [10] 2011 54.0 (46-60.3) China AASLD 2000 AMA/M2 IIF/ELISA 6 Imura-Kumada [11] 2012 56.7 ± 8.4 Japan NR M2 ELISA 7 Jong-Hon [12] 2001 NR Japan NR AMA IIF 6 Lee [13] 1983 NR America Clinical features* AMA IIF 5 Liu and Liu [14] 2010 55 ± 15 China EASL AMA IIF 7 Liu and Norman [15] 2010 NR Multicenter † EASL AMA IIF 6 Lu [16] 2017 52.94 ± 1.49 China AASLD 2009 M2 NR 7 Milkiewicz [17] 2009 48 ± 2 Canada Clinical features* M2 ELISA 6 Muratori [18] 2004 58.1 ± 14 Italy Clinical features* AMA/M2 IIF/ELISA/WB 7 Nagai [19] 1983 NR Japan Clinical features* AMA/M2 IIF/ELISA 5 Oertelt [20] 2007 67 Italy Clinical features* AMA ELISA 7 Romero-Gómez [21] 2004 55.4 ± 12.5 Spain Clinical features* AMA IIF 8 Sakugawa [22] 2003 22-88 Japan Clinical features* AMA IIF 8 Sun [23] 2019 32-76 China AASLD 2009 AMA/M2 IIF/WB 7 Tang [24] 2017 45 China AASLD 2009 M2 ELISA 8 Villalta [25] 2015 41.1 (2-87) Italy AASLD 2009 AMA/M2 IIF/Line blot 7 Wang [26] 2015 52 (44-77) China AASLD 2009 AMA/M2 ELISA/ELISA 7 Yang J [27] 2016 56.89 ± 9.87 China EASL AMA/M2 NR/NR 8 Yang Z [28] 2012 assay used for AMA (IIF or non-IIF) and M2 (ELISA or non-ELISA). The results of the meta-regression revealed that sample size (P < .001) and stud...…”
Section: Heterogeneity Analysis and Publication Biasmentioning
confidence: 99%
“…[3] The etiology of PBC remains poorly understood but is believed to involve a combination of genetic susceptibility, environmental triggers, and breakdown of immune tolerance. [4] The hallmark of PBC is the loss of immune tolerance to mitochondrial and nuclear antigens, leading to immune-mediated bile duct damage driven by autoreactive T and B cells. [5] PBC is associated with specific human leukocyte antigen alleles, suggesting a genetic component, as well as viral triggers and molecular mimicry between microbial and self-proteins.…”
Section: Introductionmentioning
confidence: 99%